To Produce an Effective Composition of Vermiculite Plita and to Study the Coefficient of Thermal Conductivity - Basic (PhD) B.A.Tursunov; Professor X.A.Akramov; Associate professor A.Ganiyev (Peerian Journals Publishing, 2022)
This paper discusses the development of an effective composition of extra-light concretes based on foamed vermiculite and its thermal conductivity coefficient.
Keywords: Foamed vermiculite; thermal conductivity coefficient; thermal conductivity resistance; foaming coefficient